2022
DOI: 10.1093/ajhp/zxac035
|View full text |Cite
|
Sign up to set email alerts
|

Detecting drug diversion in health-system data using machine learning and advanced analytics

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The linking of indications to medication orders would be able to help pharmacist better determine appropriate medication and dosing, an initiative that is supported by a patient survey 37,38 . An additional aspect that has been evaluated in the literature is the use of AI to prevent diversion of controlled substances, which is supported by guidelines and a multicenter study which found an accurate algorithm identifying cases of diversion a median of 74 days faster than existing methods 39,40 . Another area that AI can help optimize is the ability to predict medication demand and streamline inventory management, reducing the risk of medication shortages, although external factors will always need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linking of indications to medication orders would be able to help pharmacist better determine appropriate medication and dosing, an initiative that is supported by a patient survey 37,38 . An additional aspect that has been evaluated in the literature is the use of AI to prevent diversion of controlled substances, which is supported by guidelines and a multicenter study which found an accurate algorithm identifying cases of diversion a median of 74 days faster than existing methods 39,40 . Another area that AI can help optimize is the ability to predict medication demand and streamline inventory management, reducing the risk of medication shortages, although external factors will always need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 An additional aspect that has been evaluated the literature is the use of AI to prevent diversion of controlled substances, which is supported by guidelines and a multicenter study which found an accurate algorithm identifying cases of diversion a median of 74 days faster than existing methods. 39,40 Another area that AI can help optimize is the ability to predict medication demand and streamline inventory management, reducing the risk of medication shortages, although external factors will always need to be considered. An example of the role of AI throughout the medication use process can be found in Figure 2…”
Section: Discussionmentioning
confidence: 99%
“…Flowlytics ® from Invistics was developed using artificial intelligence (AI) to monitor opioid usage and to detect potential diversion. A recent study indicated that use of machine learning and advanced analytics can detect known diversion cases much faster (ranges from 7–579 days faster) than traditional diversion detection methods that use periodic reporting [ 4 ]. This new methodology has demonstrated more than 95% accuracy, specificity, and sensitivity, and is designed to alert investigators for potential drug diversion by quickly detecting: 1) Lack of or discrepancy in drug reconciliation, 2) Time-range matrix to detect significant differences in drug waste behavior from a particular provider as compared to peers in similar cases and 3) A pattern of full dose wasting where a full vial of unused medication goes into waste instead of being returned [ 5 ].…”
Section: Diversion Monitoring and Detectionmentioning
confidence: 99%
“… 42 The use of health-system data coupled with machine learning and advanced analytics has been shown to be highly accurate in detecting transactions involving a high risk of diversion. 43 Machine learning detected diversion an average of 160 days (median 74 days) faster.…”
Section: Medical Record Surveillancementioning
confidence: 99%
“… 51 Darbishire et al reported testing in pharmacy students detected 2.2 events per 100 students annually. 43 …”
Section: Drug Testingmentioning
confidence: 99%